Petrographic, Geochemical Characteristics, and Metallic Mineral Potential in the Ketel Katin Lahin of the Wahlua Formation, Buru Island - Riry, Roberth Berthy (JENDELA PENGETAHUAN, 2023)
Buru Island exhibits a high diversity of rock formations and types, with varying topography ranging from lowlands along the coastal regions, reef terraces, to high hill regions with steep to very steep slopes, which dominate the topography of Buru Island. The complex and diverse geological conditions, encompassing both the constituent rock compositions and structures, indicate that Buru Island holds a significant potential for geological and mineral resources. The aim of this research is to understand the petrographic characteristics, rock geochemistry, and potential for metallic minerals at the research site. The research consists of three stages: preparation, field investigation, and laboratory analysis. The analysis methods include Petrographic Rock Analysis and Rock Geochemical Analysis. Rock Geochemical Analysis involves chemical examination of rock samples (selected based on petrographic analysis results) to determine the major elemental (metal) content within the Wahlua formation rocks. This includes Au, Hg, As, Ba, Co, Cr, Cu, Fe, La, Mn, Ni, Pb, Sr, and Zn. The analysis of major elemental geochemistry will be conducted using AAS and ICP OES methods at the INTERTEK Laboratory (Jakarta). The research results reveal that the metal Au (gold) exhibits the highest concentration in quartz rock samples at the Ketel Katin Lahin location (Pagar Zn), with a content of 38,728 ppm or 38.728 g Au/ton of material (rock), and the lowest concentration of 6,005 ppm at the Ketel Kamang Lahim location, equivalent to 4,015 g Au/ton of material (rock).